2014
DOI: 10.1111/cas.12445
|View full text |Cite
|
Sign up to set email alerts
|

Indoleamine 2,3‐dioxygenase promotes peritoneal metastasis of ovarian cancer by inducing an immunosuppressive environment

Abstract: Indoleamine 2,3-dioxygenase (IDO) is a tryptophan-catabolizing enzyme that has immunoregulatory functions. Our prior study showed that tumoral IDO overexpression is involved in disease progression and impaired patient survival in human ovarian cancer, although its mechanism remains unclear. The purpose of the present study is to clarify the role of IDO during the process of peritoneal dissemination of ovarian cancer. Indoleamine 2,3-dioxygenase cDNA was transfected into the murine ovarian carcinoma cell line O… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
44
1
3

Year Published

2014
2014
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(48 citation statements)
references
References 35 publications
0
44
1
3
Order By: Relevance
“…Previous study also showed that phosphorylated Akt increased IDO expression in dendritic cells [20,21]. Furthermore, IDO expression was related with cancer metastasis [22,23]. Therefore, we speculated that 1-BT may also inhibit cell migration and invasion through suppressing the IDO expression in gastric cancer cells.…”
Section: Discussionmentioning
confidence: 77%
“…Previous study also showed that phosphorylated Akt increased IDO expression in dendritic cells [20,21]. Furthermore, IDO expression was related with cancer metastasis [22,23]. Therefore, we speculated that 1-BT may also inhibit cell migration and invasion through suppressing the IDO expression in gastric cancer cells.…”
Section: Discussionmentioning
confidence: 77%
“…IDO is frequently expressed in many cancers such as gastric, pancreatic, colorectal and prostate cancers (Uyttenhove, 2003), ovarian cancer (Tanazaki et al, 2014) and inflammation (Kim, 2015). To identify IDO inhibitors for therapeutic purpose we have selected IDO protein.…”
Section: Discussionmentioning
confidence: 99%
“…So, the induction of IDO by cytokines decreases the availability of TRP for serotonin synthesis (Mellor and Munn ,1999;Munn et al, 1999). Mostly IDO is expressed in many cancers like gastric, pancreatic, colorectal and prostate cancers (Uyttenhove, 2003), ovarian cancer (Tanazaki et al, 2014). The most common complication of cancer is cancer related fatigue (CRF) and its treatment that can significantly impair quality of life.…”
Section: Introductionmentioning
confidence: 99%
“…IDO, en induisant un environnement immunosuppresseur, participerait à la diffusion intrapéritonéale des cancers de l'ovaire [183].…”
Section: Modification Du Métabolisme Local Du Tryptophaneunclassified